Integrated forest biorefineries challenges and opportunities - Christopher, Lew (RSC green chemistry, 2013)
This reference book describes how bioprocessing and biotechnology could enhance the value extracted from wood-based lignocellulosic fiber by employing both biochemical and thermochemical conversion processes. It documents recent accomplishments and suggests future prospects for research and development of integrated forest biorefineries (IFBR) as the path forward for the pulp, paper and other fiber-processing industries. This is the only book to cover this area of high economic, social, and environmental importance. It is aimed at industrialists and academics from diverse science and engineering backgrounds including chemical and biotechnology companies, governmental and professional bodies, and scholarly societies.